A review of human trafficking issues in Malaysia and Nigeria - Ibrahim, Sani Sani; Ab. Halim, Adlina; Adnan, Zatul Himmah (Universiti Putra Malaysia Press, 2019)
Human trafficking is a growing transnational crime, threatening national security, causing economic losses and damaging the domestic human rights reputation of countries. It is the reflection of the problem facing the global societies today, including Malaysia and Nigeria. The countries were chosen as the study because both Malaysia and Nigeria ratified United Nations Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children. The countries subsequently enacted national policies in compliance with UN Trafficking Protocol. The aim of this article is to: (1) review the current studies of human trafficking in both countries by looking at nature, pattern, and some distinct characteristic of human trafficking in both countries; (2) outline the gap in the literature and make some suggestion for future research on human trafficking in both countries. The review of the literature is carried out based on relevant existing literature and past studies on their commitment (Malaysia and Nigeria) in responding to the UN Trafficking Protocols. The review reveals the challenges faced by both countries in combating human trafficking, are not of policy formulation but effective implementation of Anti-Trafficking in persons and Anti-Smuggling of Migrants Act and Trafficking in Persons Prohibition Law Enforcement and Administration Act (TPPLEAA) in Malaysia and Nigeria respectively. Moreover, the review shows that Protection and Assistance of Trafficked Persons, Prevention of Human Trafficking, Prosecution of Traffickers and Promotion of Partnership (4Ps) in combating human trafficking have not been adequately examined. The study suggests the ways to address human trafficking issues in both countries.